Antihypertensive effects and endothelial progenitor cell activation by intake of chicken collagen hydrolysate in pre- and mild-hypertension - Saiga Egusa, A.(Nippon Meat Packers Inc., Tsukuba, Ibaraki (Japan). R and D Center); Iwai, K; Hayakawa, T; Takahata, Y; Morimatsu, F (Bioscience, biotechnology, and biochemistry, 2009)
Chicken collagen hydrolysate was given to 15 mildly hypertensive subjects for 4 weeks. Blood pressure was significantly decreased by 11.8 mmHg (P<0.01). A reduction in plasma renin activity was observed in blood test after intake. A colony assay of endothelial progenitor cells in blood samples from non-smokers revealed an approximately 30% increase in the number of colonies.